The Effect of Liquidity on Governance - Edmans, Alex; Fang, Vivian W.; Zur, Emanuel (Review of Financial Studies, 2013)
[This paper demonstrates a positive effect of stock liquidity on blockholder governance. Liquidity increases the likelihood of block formation. Conditional upon acquiring a stake, liquidity reduces the likelihood that the blockholder governs through voice (intervention)—as shown by the lower propensity for active investment (filing Schedule 13D) than passive investment (filing Schedule 13G). The lower frequency of activism does not reflect the abandonment of governance, but governance through the alternative channel of exit (selling one's shares): A 13G filing leads to positive announcement returns and improvements in operating performance, especially in liquid firms. Moreover, taking into account the increase in block formation, liquidity has an unconditional positive effect on voice as well as exit. We use decimalization as an exogenous shock to liquidity to identify causal effects.]